Pendidikan Politik Pemula Bagi Siwa-Siswi SMU Negeri 9 Dan SMU Negeri 9 Binsus Manado: Beginner Political Education for Students of SMU Negeri 9 and Binsus Manado - Burhan Niode; Nasrun Sandiah (Vivabio: Jurnal Pengabdian Multidisiplin, 2024)
The aim of this activity is to provide an understanding of beginner voters, political participation and general elections/regional head elections, organizing general elections/regional head elections, and simulating voting in general elections and regional elections. The methods for implementing this activity are lectures, discussions, brainstorming and demonstrations. The results of providing political education material from the first session to the last session found that the majority of participants (63%) had a very good understanding of the overall material provided by the facilitator, 29% of participants had good understanding, and 8% of participants had a fairly good understanding of the entire material provided, including a demonstration of voting at a polling place (TPS). These results describe that the political education activities for novice voters went according to expectations, namely strengthening the understanding of participants, namely novice voters, regarding the implementation of general elections and regional head elections, especially the implementation of the 2024 Simultaneous General Elections and Regional Head Elections. ABSTRAK Tujuan dari kegiatan ini adalah memberikan pemahaman tentang pemilih pemula, partisipasi politik dan pemilihan umum/pemilihan kepala daerah, penyelenggara pemilihan umum/pemilihan kepala daerah, dan simulasi pemberian suara pemilihan umum dan pemilihan kepada daerah. Metode palaksanaan kegiatan ini adalah ceramah, diskusi, curah pendapat, dan demonstrasi. Hasil pemberian materi pendidikan politik dari sesi pertama sampai sesi terakhir didapati bahwa mayoritas peserta (63%) memiliki pemahaman yang sangat baik terhadap keseruhan materi yang diberikan oleh fasilitator, terdapat 29 % peserta memiliki pemahaman baik, dan 8 % peserta memiliki pemahaman yang cukup baik terhadap keseluruhan materi yang diberikan, termasuk demonstrasi pemberian suara di Tempat Pemungutan Suara (TPS).  Hasil ini mendeskripsikan bahwa kegiatan pendidikan politik bagi pemilih pemula ini berjalan sesuai dengan harapan yakni memperkuat pemahaman peserta, yakni pemilih pemula, tentang pelaksanaan pemilihan umum dan pemilihan kepala daerah, khususnya pelaksanaan Pemilihan Umum dan Pemilihan Kepala daerah Serentak Tahun 2024.